Implementation of the Dukcapil Go Digital Programs at the Payakumbuh City Government - Rahayu, Gusti; Jumiati, Jumiati (Jurnal Studi Ilmu Pemerintahan, 2023)
This study aims to evaluate and describe how the Population and Civil Registration Office of Payakumbuh City implements the Dukcapil Go Digital program. The purposive sampling method was used to select informants in this study. The information used in this study was collected through primary data obtained from direct interviews, secondary data collected through analyzing significant correspondence, and news reports. Collection, reduction, presentation, and conclusion drawing are part of the data analysis procedure. The study reveals that the Dukcapil Go Digital program implementation in Payakumbuh City could be more optimal due to Indrajit's theory's emphasis on optimizing connectivity. However, the Payakumbuh City Dukcapil has not fully utilized the provided technology, leading to insufficient access channels and community control over WhatsApp services. Additionally, the IKD application has not been fully used, resulting in a shortage of human resources. The connectivity and access channel level is also not optimal, as the community still controls services via WhatsApp, and the IKD application is not fully utilized. The Dukcapil Go Digital program requires further optimization to achieve optimal results.